Capitalizing The Sacred: Marketing Blessed Water as Religious Theraphy in Krejengan Probolinggo - Azharghany, Rojabi (JURNAL AT-TURAS, 2018)
This study considers a question of whether blessings are commodified in the ritual practices of religious therapy associated with the certain religious figures. Buying the Air Berkah (Holy Water) from Habib Hasan Al Muhdor, a religios leader of Majelis Shalawat Ahbabul Musthofa, is a continuous tradition practiced by local Muslims at Widoro  Krejengan Probolinggo. By observing this religious (or economic?) therapy, this study attempts to argue that they have been transmitting the material thing, money, into the blessing of the attendant spirit mediums. As they received blessing and magical item from the medium air berkah, they reached for wallets to make donation. This study goes to analyze the ways their stock of knowledge are constructed through ritualized practices of buying air berkah and the ways it reproduced the social structure of Krejengan community associated with their religious belief in the commodified item of blessing. It leads this study to conclusion that religion of the masses requires holy men to satisfy the needs of ordinary men and women, and hence the sacred and charisma are corrupted by the demand for miracles and spectacles through certain mechanism, including religious therapy.